Production of recombinant TSA-1 and evaluation of its potential for the immuno-therapeutic control of Trypanosoma cruzi infection in mice - Juan Jose de la Cruz; Liliana Villanueva-Lizama; Victor Dzul-Huchim; María-Jesus R; Pedro Martinez-Vega; Miguel Rosado-Vallado; Jaime Ortega-Lopez; Claudia Ivonne Flores-Pucheta; Portia Gillespie; Bin Zhan; Maria Elena Bottazzi; Peter J. Hotez; et al. (Taylor & Francis Group, 2019)
A therapeutic vaccine for human Chagas disease (American trypanosomiasis caused by Trypanosoma cruzi) is under development based on the success of vaccinating mice with DNA constructs expressing the antigens Tc24 and Tc-TSA-1. However, because DNA and nucleic acid vaccines produce less than optimal responses in humans, our strategy relies on administering a recombinant protein-based vaccine, together with adjuvants that promote Th1-type immunity. Here we describe a process for the purification and refolding of recombinant TSA-1 expressed in Escherichia coli. The overall yield (20-25%) and endotoxin level of the purified recombinant TSA-1 (rTSA-1) is suitable for pilot scale production of the antigen for use in phase 1 clinical trials. Mice infected with T. cruzi were treated with rTSA-1, either alone or with Toll-like receptor 4 (TLR-4) agonist adjuvants including monophosphoryl lipid A (MPLA), glucopyranosyl lipid A (GLA, IDRI), and E6020 (EISEI, Inc). TSA-1 with the TLR-4 agonists was effective at reducing parasitemia relative to rTSA-1 alone, although it was difficult to discern a therapeutic effect compared to treatment with TLR-4 agonists alone. However, rTSA-1 with a 10 ug dose of MPLA optimized reductions in cardiac tissue inflammation, which were significantly reduced compared to MPLA alone. It also elicited the lowest parasite burden and the highest levels of TSA-1-specific IFN-gamma levels and IFN-gamma/IL-4 ratios. These results warrant the further evaluation of rTSA-1 in combination with rTc24 in order to maximize the therapeutic effect of vaccine-linked chemotherapy in both mice and non-human primates before advancing to clinical development.